Financial Literacy Ability in Solving Mathematical Problems (Case Study of Bugisneese Gender Differences) - Arma Wangsa; Heri Retnawati; Ariyadi Wijaya; Asrul Nur Iman; Sitti Mutia Umasugi (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to analyze students' financial literacy abilities in terms of Bugisneese gender differences (oroane, makkunrai, calabai, and calalai) in solving math problems using a survey method of 309 XI graders of public senior high schools in Soppeng Regency, South Sulawesi Province. The data collection techniques were carried out using a financial literacy test and gender diversity questionnaires. The collected data were analyzed using ANOVA with the help of IBM SPSS Statistics 25 (trial version). The research results showed that there were differences in students' financial literacy abilities, especially between students with an oroane and makkunrai gender tendency. The financial literacy abilities of students who tend to gender with feminine roles (makkunrai and calabai) are better than students who tend to gender with masculine roles (oroane and calalai). These results construct the knowledge that differences in students' financial literacy abilities in terms of solving mathematics problems do not only occur in sex differences (binary gender roles) cases but also involve differences in non-binary gender roles. Therefore, gender role differences need to be considered in integrating learning mathematics with financial literacy.